1990
DOI: 10.1029/ja095ia08p12219
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the seasonal and solar cycle variations of stable aurora red arcs

Abstract: SAR arc statistics provide information on the seasonal and solar cycle variations in the subauroral region electron temperature peak and associated magnetospheric energy source. There are two sources of long‐term (solar cycle and seasonal) variability in the magnitude of the subauroral region electron temperature peak and associated SAR arc emission intensity: (1) the neutral atmosphere and ionosphere and (2) the magnetospheric energy source. The results of this study indicate that the observed seasonal variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 37 publications
11
49
1
Order By: Relevance
“…It is immediately obvious that for the same heat¯ow, the electron temperature is hotter in the presence of the low electron density in agreement with the conclusions of Kozyra et al (1990) and Fok et al (1991a, b). However, changes in the electron density do not signi®cantly eect the electron temperature (in comparison with those obtained by Kozyra et al (1997) and Fok et al (1991a, b) resulting from the given heat ux of electrons as demonstrated in Fig.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…It is immediately obvious that for the same heat¯ow, the electron temperature is hotter in the presence of the low electron density in agreement with the conclusions of Kozyra et al (1990) and Fok et al (1991a, b). However, changes in the electron density do not signi®cantly eect the electron temperature (in comparison with those obtained by Kozyra et al (1997) and Fok et al (1991a, b) resulting from the given heat ux of electrons as demonstrated in Fig.…”
supporting
confidence: 81%
“…4, where I and I/J are plotted against the number of days in the year. The reason for these variations may be due to dierences in the high-altitude heat source and to seasonal changes in the atmosphere and ionosphere (Kozyra et al, 1990).…”
Section: Results Of the Statistical Study And Discussionmentioning
confidence: 99%
“…A quantitative analysis of this interplay has been performed by Kozyra et al (1990). These authors demonstrate that it is the cooling rate of electrons to ions, not the heating rate of electrons by precipitating particles and subsequent downward heat conduction, which dominates solar cycle variations in F-region electron temperatures and solar cycle SAR arc intensities.…”
Section: Dependence Of the Electron Temperature On The Electron Densitymentioning
confidence: 97%
“…Pedersen et al (2007) reported feint optical structures as far as 10 • equatorward of the traditional auroral oval. At these temperatures there are sufficient high-energy electrons among the thermal population to excite SAR arcs (Cole, 1965;Kozyra et al, 1990). Stable auroral red (SAR) arcs are likely the subauroral optical phenomena that have been most thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%